Wage Effect of Adverse Health Indicators - Mork, Justin (My University, 2011)
In the employment market many factors can contribute to and detract from not only an individual's success in finding and maintaining employment but also advancement and wage. The purpose of this research is to assess the effects of the negative health indicators of smoking and unhealthy weight on wages and economic status.
Color poster with text and charts.
Keywords: Body image--Social aspects; Wage differentials--United States; Health status indicators; Smoking--Economic aspects; Obesity--Economic aspects; Posters